About social and cultural aspects of human nature in the context of philosophical anthropology - S. K. Kostiuchkov (Granì, 2015)
In the paper the approaches to sociocultural understanding of human nature in the context of philosophical anthropology, analyzes the essence of human nature contradictions inherent in the contradiction between biological and social components; author focuses attention on the concept of «identity» in the context of philosophical anthropology and characterization of the status of human life; put forward a reasoned statement that outlook, as the level of philosophical understanding of the world, combining both biological and social components of human nature. It is emphasized that universal principle transistorychnym public attitudes towards human life is the recognition of its absolute value in different dimensions religious, philosophical, scientific. The author notes that religious, especially biblical doctrine emphasizes the value of human life that flows from dignity of man, created in God’s image, a rational being who comes to Earth as, in a sense, a representative of God. The article stresses the urgency of a new philosophical paradigm as an important ideological guideline that requires perceive and understand the biological basis of man is not as indispensable, but neutral background of social life, but as a basis upon which and through which a person is transformed into a cultural and civilized being.